Safe drinking water: Experience with Water Safety Plans and assessment of risk factors in water supply - María J. Gunnarsdóttir 1947- (2012)
Access to adequate and clean drinking water is one of the fundamentals of a good and prosperous society. A comprehensive regulatory framework as well as institutional guidelines and procedures are necessary to secure this at any time. Iceland was one of the first countries to categorize drinking water as food in legislation passed in 1995. According to the legislation water utilities are obligated to implement systematic preventive management, Water Safety Plan (WSP), to ensure good quality water in conjunction with the regular external control by the regulator. The aim of the research is to evaluate the effect of the legislation on the utilities and whether it has had a measurable effect on the quality of drinking water and on public health. Part of the research is to look at risk from microbiological pollution and how far it can travel with groundwater. This is accomplished by using a model that incorporates hydrological and geological factors and comparing the results with an actual faecal contamination of drinking water that caused a norovirus outbreak in Iceland. The results of the research confirm several quantifiable beneficial effects of WSP on water quality and public health as well as on operation of water utilities. It analysis what has to be in place for successful operation of WSP and what obstacles were significant.The study of mobility of microorganisms in groundwater and comparison with an actual outbreak showed the necessity to take into account that microorganisms live longer in colder water and that due to their smaller size viruses can travel further than other pathogens through coarse geological strata. Aðgangur að nægu og hreinu drykkjarvatni er ein af undirstöðum velferðar í hverju samfélagi. Mikilvægt er að tryggja að vatn njóti verndar bæði lagalega og í allri umgengi um vatnsauðlindina. Ísland flokkaði neysluvatn sem matvæli í matvælalöggjöf 1995. Með þeirri löggjöf voru lagðar skyldur á vatnsveitur að beita kerfisbundu fyrirbyggjandi innra eftirliti til að tryggja gæði neysluvatns ...